Hodnocení finanční situace podniku pomocí nástrojů finanční analýzy a následná formulace návrhů na zlepšení. - Míchal, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato bakalářské práce se zaměřuje na finanční analýzu vybraného podniku za fiskální období od 31.3. 2013 do 31.3.2018. Práce je rozdělena na čtyři základní části. V první části jsou vymezeny cíle a metodika práce, dále jsou uvedeny a podrobně popsány jednotlivé nástroje finanční analýzy, které jsou v práci použity. Následuje samotná finanční analýza, kdy se zhodnotí aktuální ekonomický stav podniku. A závěrečná část obsahuje vlastní návrhy na zlepšení ekonomického chodu podniku, což je zároveň cíl celé práce.

This bachelor thesis is focused on financial analysis of selected company in fiscal period from 31.3.2013 to 31.3.2018. The thesis is devided into four basic parts. The goals and metodology are defined in the first part, individual instruments of financial analysis used in this thesis are described in the detail in the next part. Followed by financial analysis itself, which evaluates the current economic situation of the company. And the final part contains personal suggestions for improvement of economic business in company, what actually main goal of the thesis.
Evaluation of the financial situation of the company by using tools of financial analysis and subsequent formulation of proposals for improvement.
Keywords: finanční analýza; rozvaha; výkaz zisku a ztrát; peněžní toky; absolutní ukazatele; poměrové ukazatele; rozdílové ukazatele; finanční zdraví podniku; financial analysis; balance sheet; profit and loss statement; cash flow; absolutely indicators; differential indicators; ratio indicators; financial health of company